Makna Komunikasi Antarpersona dalam Membina Hubungan Persahabatan - Naufal Fahrurrobby; Alex Sobur (Bandung Conference Series: Public Relations, 2023)
Abstract. This research is entitled Interpersonal Communication Meaning in Building Friendship (Roland Barthes' Semiotics Analysis in The Bad Guys Film). The purpose of this research is to find out denotative meaning, connotative meaning and interpersonal communication myth in building friendship in The Bad Guys film. The Bad Guys film describe the friendship story of a famous animal bandits, The Bad Guys, the members are Mr. Wolf, Mr. Snake, Mr. Shark, Mr. Piranha and Mrs. Tarantula. This film tells there is a conflict that arise because of the misunderstanding among the gang and it causes the strained of their friendship, thus the characters in this film applied interpersonal communication in solving the conflict. Constructivist paradigm is applied to this research with qualitative descriptive method and Roland Barthes' semiotics approach. The data collecting technique employed in this research is observing and literary study. The researcher did the direct research to the research object intended to collect the required information. The result of this research shows there are denotative meaning, connotative meaning, and the meaning of interpersonal communication myth in building friendship in "The Bad Guys" film. This film also depicts there are openness, empathy, supportive attitude, positive attitude and equality. The interpersonal communication meaning can be seen from the sign and meaning which have been analyzed with Roland Barthes' theory of semiotics. Abstrak. Penelitian ini berjudul Makna Komunikasi Antarpersona dalam Membina Hubungan Persahabatan (Analisis Semiotika Roland Barthes Pada Film “The Bad Guys”). Tujuan dalam penelitian ini yaitu untuk mengetahui makna denotasi, konotasi, dan mitos komunikasi antarpersona dalam membina hubungan persahabatan pada film “The Bad Guys”. Film “The Bad Guys” menggambarkan kisah persahabatan geng penjahat hewan terkenal dengan nama The Bad Guys yang beranggotakan Mr. Wolf, Mr. Snake, Mr. Shark, Mr. Piranha, dan Mrs. Tarantula. Dalam film ini menceritakan adanya konflik yang timbul akibat kesalahpahaman diantara kelima sahabat tersebut dan menyebabkan hubungan persahabatan mereka menjadi renggang sehingga tokoh dalam film ini menggunakan komunikasi antarpersona dalam menyelesaikan konflik tersebut. Pada penelitian ini menggunakan paradigma konstruktivis dengan metode penelitian kualitatif deskriptif dan pendekatan analisis semiotika Roland Barthes. Teknik pengumpulan data yang dilakukan yaitu dengan observasi dan studi pustaka. Penulis melakukan penelitian langsung terhadap objek penelitian untuk mendapat informasi yang dibutuhkan. Hasil penelitian menunjukan terdapat makna denotasi, konotasi, dan mitos makna komunikasi antarpersona dalam membina hubungan persahabatan pada film “The Bad Guys”. Film ini juga menggambarkan adanya keterbukaan, empati, sikap mendukung, sikap positif, dan kesetaraan. Makna komunikasi antarpersona tersebut dapat dilihat dari tanda dan makna yang telah dianalisis menggunakan teori semiotika Roland Barthes.